Pengaruh Pengarsipan Yang Terorganisir Terhadap Kinerja Karyawan Di Kantor Lab Bisnis Politeknik Negeri Bandung - Muhammad Rosyid Ash-Shodiq; Dimas Prasetia Caraka (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
Effective document management plays an important role in the smooth running of an organization and the performance of its employees. The aim of this research is to determine the impact of records management on employee performance. We investigated record-keeping practices at the Polban Business Lab office through participatory observation methods. Observations show the need to improve the system for storing, recording, maintaining and depreciating records. Centralized storage systems and lack of logs make access difficult and degrade performance. Poor maintenance and inefficient filing increase the risk of losing information and slow down workflow. In short, increasing the effectiveness of employee performance and maintaining the continuity of organizational information requires improved records management, including the use of computer technology, better records management, routine maintenance, and effective records management.